2007
DOI: 10.1007/s00210-007-0204-4
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the second extracellular loop of the histamine H2 receptor do not affect the species-selective activity of guanidine-type agonists

Abstract: Residues in the second extracellular loop (e2) play a role in ligand binding in certain aminergic G protein coupled receptors (GPCRs). N-[3-(1H-Imidazol-4-yl)propyl)]guanidines and N (G)-acylated derivatives are more efficacious and potent agonists at fusion proteins of the guinea pig histamine H(2) receptor and the short splice variant of G(salpha), G(salphaS) (gpH(2)R-G(salphaS)) than at the human isoform (hH(2)R-G(salphaS)). To elucidate the structural basis for this species-selectivity, we generated a muta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Ovalbumin (purity Ͼ98%; EndoGrade) was obtained from Hyglos (Regensburg, Germany) and dissolved at a concentration of 1 mg/ml in PBS, pH 7.4. [␥-32 P]GTP was synthesized as described previously (Preuss et al, 2007). […”
Section: Methodsmentioning
confidence: 99%
“…Ovalbumin (purity Ͼ98%; EndoGrade) was obtained from Hyglos (Regensburg, Germany) and dissolved at a concentration of 1 mg/ml in PBS, pH 7.4. [␥-32 P]GTP was synthesized as described previously (Preuss et al, 2007). […”
Section: Methodsmentioning
confidence: 99%
“…32 P]GTP was synthesized as described previously (Preuss et al, 2007b). [ 3 H]Mepyramine (30.0 Ci/mmol) was from PerkinElmer Life and Analytical Sciences (Walatham, MA).…”
Section: Materials [␥-mentioning
confidence: 99%
“…For the muscarinic M 3 receptor, several amino acids in the E2-loop are important for efficient agonist-induced activation of the muscarinic M 3 receptor (Scarselli et al, 2007). In contrast to these results, the E2-loop does not contribute to the species selectivity of guanidine-type agonists at human and guinea pig histamine H 2 receptor (Preuss et al, 2007). Our present study shows that the E2-loop and the E2-loop in combination with the N terminus have ligand-specific influence on the pharmacology of the H 1 R. Based on these data, it can be concluded that the extracellular loop E2 as well as the N terminus contribute to ligand binding, receptor activation, and selectivity in biogenic amine and nucleoside GPCRs.…”
Section: Straßer Et Almentioning
confidence: 70%
“…[␥-32 P]GTP was synthesized as described previously (Preuss et al, 2007), and [ 3 H]mepyramine (30.0 Ci/mmol) was obtained from PerkinElmer Life and Analytical Sciences (Waltham, MA). A Rotiszint ecoplus (Roth, Karlsruhe, Germany) liquid scintillation cocktail was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation